Effect of educational session on antimicrobial consumption pattern in the medical intensive care unit of government tertiary care hospital, Jaipur, Rajasthan - Shashank Sahu; Rathi, Priyanka; Jakhar, Punam; Kumar, Susheel; Rathore, Rajveer Singh; Saran, Divya (Asian Journal of Medical Sciences, 2022)
Background: Polypharmacy and inappropriate usage of antibiotics are common in an intensive care unit which may increase morbidity, mortality, antimicrobial resistance, and treatment cost. Aims and Objectives: The objective of the present study is to evaluate the Effect of Educational Session on Antimicrobial consumption pattern in the Medical Intensive Care unit (MICU) of Government Tertiary Care hospital, Jaipur, Rajasthan. Materials and Methods: An interventional study was conducted over a period of 18 months, and the data were obtained from Medical Record Department (MRD) and from the MICU after organizing an educational session, of a tertiary care hospital. All the data were tabulated in summery sheets and were analyzed using computer software SPSS version 20 and Microsoft Excel 2019. Results: A total 257 cases were reviewed during the study period; among these 46.77% were males and 53.23% were females in MRD group, out of 124 cases and 53.38% were males and 46.62% were females in MICU group, out of 133 cases. In MRD group mean age of patients was 56.16 and in MICU group mean age of patients was 56.00 years. Discussion: A total of 616 antimicrobial drugs were prescribed, out of which Amoxiclav was most frequently given in MRD group and Meropenem was most frequently given in MICU group. Conclusion: This study gave an overview of antimicrobial use in the MICU and helped to find out the consumption pattern that would spread awareness among the prescribers.